Optimal coordinated voltage control in active distribution networks using backtracking search algorithm - Hashim T.J.T.; Mohamed A. (Public Library of Science, 2023)
comparative effectiveness; data analysis software; algorithm; computer simulation; electricity; equipment design; power supply; Algorithms; Computer Simulation; Electric Power Supplies; Electricity; Equipment Design